Brigatinib treatment in a patient with advanced NSCLC with XPO1-ALK fusion: a case report - Yang Zhang; Ke-jie Li; Can Wang; Chang-lin Zou; Meng Su (Frontiers in Oncology, 2025)
Patients with ALK-rearranged non-small cell lung cancer (NSCLC) who are treated with ALK tyrosine kinase inhibitors (ALK TKIs) have better prognoses. In this case report, we provide evidence of a novel ALK fusion, XPO1-ALK (intergenic), identified by next-generation DNA sequencing in a patient with advanced lung cancer. After 5 months of brigatinib targeted therapy, the patient clearly experienced tumor disintegration, and this treatment resulted in partial remission. To date, this patient has experienced 5 months of progression-free survival after brigatinib treatment. In addition to reporting the identification of a novel ALK fusion, XPO1-ALK (intergenic), and the sensitivity and safety of brigatinib treatment for lung cancer, this study increased the list of known ALK fusion partners in ALK-positive NSCLC. This case report has a significant clinical reference.